Resolution of disputes in the field of intellectual property - Zadnipriana-Korinna, Mariana (My University, 2022)
Today, socalled intangible assets, namely intellectual property objects, play an important role in business. We propose to consider the issue of legal protection of intellectual property in detail in this article and to analyze the mechanism of solving problems in the area. Intellectual property means copyright and patent rights, related rights, and the right to marketing designations. All these are important components of competitive struggle in the business sphere. For business entities, effective legal protection of intellectual property is one of the most important conditions for successful market positioning and profit growth.Specialists in this field are convinced of the necessity of mandatory preventive measures for the protection of intellectual property. Theresolution of disputes in the field of intellectual property with the participation of specialists makes it possible to use all promising options to get out of the situation with the least losses and with a possible benefit.The range of issues with which a specialist of this specialization works is quite wide. These can be appeals against decisions of Ukrpatent regarding the registration of intellectual property objects, resolution of conflicts related to the violation of the exclusive right to a trademark, as well as the recognition of certain situations as unfair competition.With the gaining of independence, a new stage in the development of the judicial system began in Ukraine, including an increase in the role of the court in resolving disputes through conciliation (mediation). In 2005, another judicial reform was carried out in Ukraine, as a result of which administrative courts were created, the powers of which included consideration of administrative cases regarding the appeal of any decisions, actions or inaction of subjects of power, except for cases when such decisions , actions or inaction, the Constitution or laws of Ukraine establish a different procedure for court proceedings . In particular, only in the edition of December 15, 2017 of the Code of Administrative Procedure of Ukraine does the court have a real opportunity to take an active part in the reconciliation procedure. Until now, the court did not have access to the procedure for discussing reconciliation, in fact, it was only provided with a ready-made document on the achievement of reconciliation between the parties, after which the obligation to close the proceedings arose. That is, before the adoption of the above changes, resolving the dispute through conciliation remained the exclusive prerogative of the parties in the case. Currently, the court has the opportunity not only to observe the actions of the parties to find ways of reconciliation, but also to help them understand the essence of the dispute and offer possible options for its resolution

Сьогодні важливу роль у бізнесі відіграють так звані не матеріальні активи, а сааме об’єкти інтелектуальної власності. Пропонуємо у цій статті детально розглянути питання правової охорони інтелектуальної власності та проаналізувати механізм вирішення проблем у цій сфері. Інтелектуальна власність означає авторські та патентні права, суміжні права та право на маркетингові позначення. Усе це є важливими складовими конкурентної боротьби у сфері бізнесу. Для суб'єктів господарювання ефективний правовий захист інтелектуальної власності є однією з найважливіших умов успішного позиціонування на ринку та зростання прибутку. Фахівці в цій галузі переконані в необхідності обов'язкових превентивних заходів щодо захисту інтелектуальної власності. Вирішення спорів у сфері інтелектуальної власності за участю спеціалістів дає можливість використати всі перспективні варіанти виходу із ситуації з найменшими втратами та можливою вигодою. Коло питань, з якими звертається спеціаліст даної спеціалізації творів досить широка. Це можуть бути оскарження рішень Укрпатенту щодо реєстрації об’єктів інтелектуальної власності, вирішення конфліктів, пов’язаних із порушенням виключного права на торговельну марку, а також визнання окремих ситуацій недобросовісною конкуренцією. Із здобуттям незалежності в Україні розпочався новий етап у розвитку судової системи, зокрема підвищення ролі суду у вирішенні спорів шляхом примирення (медіації). У 2005 році в Україні була проведена чергова судова реформа, в результаті якої були створені адміністративні суди, до повноважень яких входив розгляд адміністративних справ про оскарження будь-яких рішень, дій чи бездіяльності суб'єктів владних повноважень, крім випадків, коли для таких рішень, дій чи бездіяльності Конституцією чи законами України встановлено інший порядок судового розгляду. Зокрема, лише в редакції Кодексу адміністративного судочинства України від 15 грудня 2017 року суд має реальну можливість брати активну участь у процедурі примирення. До цього часу суд не мав доступу до процедури обговорення примирення, фактично надавався лише готовий документ про досягнення примирення сторін, після чого виникло зобов’язання закрити провадження. Тобто до прийняття вищевказаних змін вирішення спору шляхом примирення залишалося виключною прерогативою сторін у справі. Наразі суд має можливість не лише спостерігати за діями сторін щодо пошуку шляхів примирення, а й допомогти їм зрозуміти суть спору та запропонувати можливі варіанти його вирішення
Keywords: кафедра економіки і права; intellectual property; court; protection of rights; participants in the process; legislation; інтелектуальна власність; суд; захист прав; учасники процесу; законодавство